Pendekatan Analitik Sintetik sebagai Metode Memahami Al-Qur’an dalam Pembelajaran Kurikulum Merdeka Jenjang Sekolah Dasar - Hanifah, Hanifah; Bahar, Herwina (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to delve into the Analytic Synthetic approach as a method of understanding the Al-Qur'an in the Independent Curriculum in Elementary Schools. This article is a literature study using a descriptive method, as a qualitative study in the form of library research. This research produces information in the form of notes and descriptive data from the texts being studied. This research is expected to provide input for elementary schools using the Independent Curriculum to increase students' interest in studying the Al-Qur'an.